Development and properties of functional yoghurt enriched with postbiotic produced by yoghurt cultures using cheese whey and skim milk - Sadighbathi, Sepideh; Saris, Per E. J.; Amiri, Saber; Yousefvand, Amin (Frontiers in Microbiology, 2023)
This study aimed to examine the effects of supplementation of postbiotics derived from Streptococcus thermophilus (ST) and Lactobacillus delbrueckii subsp. bulgaricus (LB) in cheese whey (CW) and skim milk (SM) on antioxidant activity, viability of yoghurt starters, and quality parameters of low-fat yoghurt during 22 days of storage. The LB-CW (L. delbrueckii ssp. bulgaricus. L. bulgaricus postbiotic-containing cheese whey) sample exhibited the highest antioxidant activity, with 18.71% inhibition (p > 0.05). This sample also showed the highest water holding capacity (77.93%; p < 0.05) and a trend towards receiving the most favorable sensory attributes (p > 0.05) compared to the other samples. The LB-CW and LB-SM yoghurt samples exhibited significantly higher body and texture scores compared to the ST-SM-fortified yoghurt (p < 0.05). However, there was no significant difference in the overall acceptability of the LB-SM and ST-SM yoghurt samples across both starters (p > 0.05). Such findings highlight the potential of postbiotics as functional ingredients to enhance the nutritional and sensory aspects of yoghurt, further contributing to its appeal as a health-promoting product.